Dimeric ferrochelatase bridges ABCB7 and ABCB10 homodimers in an architecturally defined molecular complex required for heme biosynthesis - Nunziata Maio; Ki Soon Kim; Gregory Holmes-Hampton; Anamika Singh; Tracey A. Rouault (Haematologica, 2019)
Loss-of-function mutations in the ATP-binding cassette (ABC) transporter of the inner mitochondrial membrane, ABCB7, cause X-linked sideroblastic anemia with ataxia, a phenotype that remains largely unexplained by the proposed role of ABCB7 in exporting a special sulfur species for use in cytosolic iron-sulfur (Fe-S) cluster biogenesis. Here, we generated inducible ABCB7-knockdown cell lines to examine the time-dependent consequences of loss of ABCB7. We found that knockdown of ABCB7 led to significant loss of mitochondrial Fe-S proteins, which preceded the development of milder defects in cytosolic Fe-S enzymes. In erythroid cells, loss of ABCB7 altered cellular iron distribution and caused mitochondrial iron overload due to activation of iron regulatory proteins 1 and 2 in the cytosol and to upregulation of the mitochondrial iron importer, mitoferrin-1. Despite the exceptionally large amount of iron imported into mitochondria, erythroid cells lacking ABCB7 showed a profound hemoglobinization defect and underwent apoptosis triggered by oxidative stress. In ABCB7-depleted cells, defective heme biosynthesis resulted from translational repression of ALAS2 by iron regulatory proteins and from decreased stability of the terminal enzyme ferrochelatase. By combining chemical crosslinking, tandem mass spectrometry and mutational analyses, we characterized a complex formed of ferrochelatase, ABCB7 and ABCB10, and mapped the interfaces of interactions of its components. A dimeric ferrochelatase physically bridged ABCB7 and ABCB10 homodimers by binding near the nucleotide-binding domains of each ABC transporter. Our studies not only underscore the importance of ABCB7 for mitochondrial Fe-S biogenesis and iron homeostasis, but also provide the biochemical characterization of a multiprotein complex required for heme biosynthesis.